Opportunities and Challeges of Using Artificial Intelligence in Assessment - Supianto Supianto (IKIP PGRI Bojonegoro, 2023)
Abstract: The application of Artificial Intelligence (AI) in learning assessment has attracted the attention of many educational experts, researchers and practitioners. This study discusses the opportunities and challenges of using AI in learning assessment. Traditional assessment has weaknesses in terms of misjudgment, inability to measure individual abilities that are not measured in certain forms of assessment, significant cost and time, slow feedback, and inability to be adjusted individually. Several studies have shown that the use of AI in assessments can improve the accuracy, validity and reliability of assessments, reduce human rater bias, enable adaptive assessments, increase time and cost efficiency, provide faster and more timely feedback, and assist in identifying individual needs and improve the quality of learning. However, the use of AI technology can only be a tool, and the final decision must still be made by humans. Therefore, the use of AI in assessment requires special attention in terms of ethics and the development of human capabilities to understand and use AI technology wisely.Keywords: Artificial Intelligence, Assessment Abstrak: Penerapan Artificial Intelligence (AI) dalam penilaian pembelajaran telah menarik perhatian banyak ahli pendidikan, peneliti, dan praktisi. Penelitian ini membahas peluang dan tantangan penggunaan AI dalam asesmen pembelajaran. Asesmen tradisional memiliki kelemahan dalam hal kesalahan penilaian, ketidakmampuan mengukur kemampuan individu yang tidak terukur dalam bentuk asesmen tertentu, biaya dan waktu yang signifikan, umpan balik yang lambat, dan ketidakmampuan untuk disesuaikan secara individual. Beberapa penelitian menunjukkan bahwa penggunaan AI dalam asesmen dapat meningkatkan akurasi, validitas, dan reliabilitas asesmen, mengurangi bias penilai manusia, memungkinkan asesmen adaptif, meningkatkan efisiensi waktu dan biaya, memberikan umpan balik yang lebih cepat dan tepat waktu, serta membantu dalam mengidentifikasi kebutuhan individu dan meningkatkan kualitas pembelajaran. Namun, penggunaan teknologi AI hanya dapat menjadi alat bantu, dan keputusan akhir tetap harus dilakukan oleh manusia. Oleh karena itu, penggunaan AI dalam asesmen memerlukan perhatian khusus dalam hal etika dan pengembangan kemampuan manusia dalam memahami dan memanfaatkan teknologi AI dengan bijak.Kata Kunci: Kecerdasan Buatan, Asesmen